Análise da morfodinâmica estuarina e variação de linha de Costa do Delta do rio São Francisco - Cavalcante, Aline da Silva Inácio (2019)
The coastal environment not only by its natural interaction but also by factorsAnthropic conditions consists of a complex environment. This research aims to analyze the estuarine morphodynamics and shoreline variation at the São Francisco River mouth. The analyses consist of correlating the ten years of river discharge from between 2009 and 2018, extraction of shorelines by processing the Difference IndexNDWI) and estimating the interannual variation in the width of the São Francisco Delta. NDWI estimation was based on the images of the RapidEye satellite REIS sensor, performing a contour extraction procedure. The analyze of the estuarine morphodynamics is performed through a mathematical method to extract the shorelines. Results found evidence that the flows during the study period suffered abrupt variations and can be partitioned in three distinct cycles: high flow above 1500 m3/s (2009-2012), the transition period between 1.500 m3/s and 1.000 m3/s (2013-2015) and low flow below 900 m3/s (2006-2018). The shorelines suffered significant variations with increases and decrease of the areas near the mouth and were more intense from 2013. The width of the São Francisco Delta showed a direct correlation with the flow pattern and river capacity to carry sediment towards the mouth. During the period of high flow, the sediment removed by the coastal drift near the mouth was naturally recomposed by the material exported by the river, keeping the width of the delta stable. On the other hand, after the flow reduction, the sediment load towards the mouth reduced, inhibiting sediment replacement and causing an increase in delta width.